Body art, existência e conhecimento :a percepção do corpo na Educação Física - Medeiros, Rosie Marie Nascimento de (2005)
In the Renaissance, the anatomy project a map of the body. Since then, the human body has been investigated for innumerable techniques, configuring new landscapes on the condition human being and the proper knowledge. In accordance with Merleau-Ponty (1975), All technique is body technique. It configures and extends the Metaphysical structure of our meat. In this direction, any intervention in the human body, a tattooing, a surgery or a performance, extends the perception and the directions of the existence of the subject. Merleau-Ponty (1975) still affirms, that all technique presents objective interventions. However, the body, ahead of these interventions, doesn t have to be considered only object, but subject that, from the interventions, attributes sensible and meanings through the movements, also being this its way of being in the world. Searching to extend this reflection on the discontinuities between the object body and the subject body, as well as, with the objective to reflect on the relation between the corporal techniques and the production of the subjectivity and the knowledge of the physical education, we reflect on the body art, as one technique of body that marks the exterior of the body, exteriorizing the subjectivity, to search new means to the body and that ahead of this, we believe being able to project innumerable directions for the corporal transformations in the contemporarily. As a method for our reflection in we will support them in the phenomenology. IT presents as a new ontology, in which distinction does not occur enters the operating paper of the citizen that knows and the influence of the known object. The phenomenological understanding of body will be able to contribute with the knowledge of the Physical Education, a time that gives us important arguments on the experience of the body in relation with the nature, the culture, history. To be a body is to be tied to a world that we do not possess completive, but that we do not cease to search it